Eksistensi Modal Sosial Atas Kewajiban Ppn Dalam Menjaga Kelangsungan Usaha - Danny Wibowo (Owner : Riset dan Jurnal Akuntansi, 2023)
This research uses a phenomenological qualitative approach with interviews and direct observation methods conducted with taxable entrepreneurs in the province of East Nusa Tenggara which focuses on the utilization of social values in responding to changes in VAT regulations from the perspective of social capital. VAT is a burden that makes it possible for taxable entrepreneurs to avoid it, because it is considered that the 10% VAT is not in favor of PKP which has an impact on the selling price due to the additional VAT costs. The social capital of business actors is established through social relations between human beings in the business environment and leads to the norms and values of life with the surrounding community. Social capital is formed in the social environment where there is trust in one another. Social interaction, both economic and non-economic, is determined by the trust of business actors, consumers or the community around where the business operates. Actively contributing to various social activities is a way for businesses to mingle with society. Through social interaction with various actions and involvement in social activities for the surrounding environment to obtain and maintain legitimacy in the form of kinship, trust, values and norms for PKP businesses which have a positive impact on business continuity, despite the VAT rate which makes the selling price more expensive from non-PKP.